1997
DOI: 10.1074/jbc.272.16.10746
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Endoplasmic Reticulum Calcium Pump Expression during T Lymphocyte Activation

Abstract: Calcium mobilization from intracellular storage organelles is a key component of the second messenger system inducing cell activation. Calcium transport ATPases associated with intracellular calcium storage organelles play a major role in controlling this process by accumulating calcium from the cytosol into intracellular calcium pools. In this study the modulation of the expression of the sarco-endoplasmic reticulum calcium transport ATPase (SERCA) isoenzymes has been studied in lymphocytes undergoing phorbol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…Furthermore, Ets-1 is expressed in the lymphoid organs and in hematopoietic cells (47). This pattern of expression is very similar to that of SERCA3 (3)(4)(5)(6)(7)(8)(9)(10). Because functional EBSs had been identified in numerous promoters of genes that are involved in angiogenesis (see above), these observations, taken together, strongly suggested that Ets-1 was a good candidate for regulating the SERCA3 gene in endothelial cells.…”
Section: Ets-1 and Sp1 Control Serca3 Gene Transcriptionsupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, Ets-1 is expressed in the lymphoid organs and in hematopoietic cells (47). This pattern of expression is very similar to that of SERCA3 (3)(4)(5)(6)(7)(8)(9)(10). Because functional EBSs had been identified in numerous promoters of genes that are involved in angiogenesis (see above), these observations, taken together, strongly suggested that Ets-1 was a good candidate for regulating the SERCA3 gene in endothelial cells.…”
Section: Ets-1 and Sp1 Control Serca3 Gene Transcriptionsupporting
confidence: 53%
“…The SERCA2 gene gives rise to the ubiquitous SERCA2b isoform and to SERCA2a, which is produced mainly in cardiac, slow skeletal, and smooth muscle cells. SERCA3 is present in specific cell types such as: endothelial cells of a wide variety of tissues (4,5); epithelial cells of the trachea, salivary glands, and intestine (4,6); platelets and the hematopoietic cell lineage (7,8); pancreatic ␤-cells and the acini of salivary glands (9); and brain Purkinje cells (6). SERCA3 is expressed early in development, and it is present in the heart tube and in the yolk sac at 10 days post-coitum.…”
mentioning
confidence: 99%
“…First, SERCA3 has been shown to be expressed in different cells of haematopoietic origin. Secondly, modulations of SERCA3 expression have been found in platelets of spontaneously hypertensive rats [19,23], and upon lymphocyte activation [61] or granulocytic and monocyte\macrophage differentiation [62]. Accordingly, the analysis of the 5h-untranslated promoter region of the human SERCA3 gene revealed multiple sites for transcription factors including specific haematopoietic factors GATA and Ets.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Treatments-Lymphocyte activation and induction of HL-60 cell differentiation were performed as previously described (24,25).…”
Section: Methodsmentioning
confidence: 99%